Pengaruh Pelatihan Kader terhadap Pengetahuan dan Sikap tentang Deteksi Dini Gangguan Jiwa di Kelurahan Pajajaran Wilayah Kerja Puskesmas Pasirkaliki Kota Bandung Tahun 2019 - Susi Susanti; Nani Avianti; Muryati Muryati (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
This study is to reveal the impact of the candidate training of mental illness early detection to participants’ cognitive and behaviour towards mental illness detection. It is expected that participants able to recognize the symtomp of mental illness and detect in early stage to tackle it.  The candidate could identify as part of mental health service then report this to the nearest Puskesmas. This would solve some problems of mental health in community in detecting the indication that occurs and influence the community in 10 hamlets which have 24 integrated healthcare centre covered 25.753 population. This big sub-district that lays near education area and having immigrant from other areas has potential to raise the psychosocial problems as mental illness.The research population is 80 of participants or candidates by proportional sampling and use quasi-experimental dengan one group pretest and posttest design. The statistic test used is Wilcoxon Signed Ranks Test to test the candidates’ cognitive and pairs sample t for candidates’ behavior. The result showed that candidates’ cognitive increased significantly after they discussed in small groups with the module of early detection (Pvalue = 0,000<0,05). The behavior has increased significantly as well with the same method (Pvalue = 0,008<0,05).